A new formula for assessing skeletal age in growing infants and children by measuring carpals and epiphyses of radio and ulna. (April 2016) - De Luca, Stefano; Mangiulli, Tatiana; Merelli, Vera; Conforti, Federica; Velandia Palacio, Luz Andrea; Agostini, Susanna; Spinas, Enrico; Cameriere, Roberto
Abstract: The aim of this study is to develop a specific formula for the purpose of assessing skeletal age in a sample of Italian growing infants and children by measuring carpals and epiphyses of radio and ulna. A sample of 332 X-rays of left hand-wrist bones (130 boys and 202 girls), aged between 1 and 16 years, was analyzed retrospectively. Analysis of covariance (ANCOVA) was applied to study how sex affects the growth of the ratio Bo/Ca in the boys and girls groups. The regression model, describing age as a linear function of sex and the Bo/Ca ratio for the new Italian sample, yielded the following formula: Age = −1.7702 + 1.0088 g + 14.8166 (Bo/Ca). This model explained 83.5% of total variance (R 2  = 0.835). The median of the absolute values of residuals (observed age minus predicted age) was −0.38, with a quartile deviation of 2.01 and a standard error of estimate of 1.54. A second sample test of 204 Italian children (108 girls and 96 boys), aged between 1 and 16 years, was used to evaluate the accuracy of the specific regression model. A sample paired t-test was used to analyze the mean differences between the skeletal and chronological age. The mean error for girls is 0.00 and the estimated age is slightly underestimated in boys with a mean error of −0.30 years. The standard deviations are 0.70 years for girls and 0.78 years for boys. The obtained results indicate that there is a high relationship between estimated and chronological ages. Highlights: 332 X-rays of left hand-wrist bones were analyzed. Repeatability and reproducibility are high for intra- and inter-observer error. A new specific linear regression formula was developed. Its accuracy was tested in a second sample of 204 infants and children. The standard deviations are 0.70 years for girls and 0.78 years for boys.